Generation, implementation, and appraisal of an N-gram-based stemming algorithm. - Pande, Bhagwati P; Tamta, Pawan; Dhami, Hoshiyar S (Digital Scholarship in the Humanities, 2019)
A language-independent stemmer has always been looked for. Single N -gram tokenization technique works well; however, it often generates stems that start with intermediate characters, rather than initial ones. We present a novel technique that takes the concept of N -gram stemming one step ahead and compare our method with an established algorithm in the field, say, Porter's stemmer for English, Spanish, and Portuguese languages. Results indicate that our N -gram stemmer is comparable with the Porter's linguistic stemmer.